Benchmarking lighting design software. (Chartered Institution of Building Services Engineers, 2000)
This document is intended to provide guidance to lighting designers and manufacturers on the accuracy of computer based simulations of illuminance levels in office spaces. It provides a data set which can be used to assess the overall performance of simulation software against a set of standard parameters. It will assist designers, manufacturers and software developers to develop a more thorough awareness of the performance of simulation tools. Use of the benchmark data is likely to contribute to improvements in the prediction of actual illuminance levels in offices, reducing the risk of disputes arising from perceived failures of designs or installations, and improving the quality of lighting installations and levels of client and user satisfaction with completed installations. It will also contribute to more effective predictions of illuminance which may lead to reductions in the energy use of the installation.